METHODOLOGICAL ASPECTS OF TEACHING PHYSICS BASED ON INNOVATIVE APPROACHES - Gulnora Gaybulova Sadullayevna (Web of Journals Publishing, 2025)
This article examines the role of innovative pedagogical approaches in physics education and the methodological aspects of their practical implementation. The modern education system places special emphasis on fostering students' active participation, independent thinking, and practical skills. In this process, interactive methods, the STEAM approach, digital technologies, and virtual laboratories play a crucial role. The article provides recommendations for organizing lessons based on innovative approaches, as well as criteria for evaluating their effectiveness. The research findings may contribute to the modernization of physics education.
Keywords: Innovative approaches, physics education, interactive methods, STEAM, digital technologies, virtual laboratories, methodology, teaching effectiveness, practical skills, scientific thinking.